MONITORING SEISMOTECTONIC PROCESSES IN THE TRANSCARPATHIAN INNER TROUGH BASED ON THE RESULTS OF COMPLEX GEOPHYSICAL OBSERVATIONS - Ihnatyshyn, V.; Malytskyy, D.; Izhak, Т.; Ihnatyshyn, М.; Ihnatyshyn, А. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article is devoted to the study of relations between the parameter variations of geophysical fields and the geodynamic state of the Transcarpathian Inner Trough. The research aims at studying the relations between the geodynamic state, observed meteorological parameters, and seismic phenomena in the Transcarpathian Inner Trough. Exploration target: seismotectonic processes in the region based on the results of monitoring geophysical fields. The scope of research includes the spatiotemporal distribution of local seismicity, modern lateral movements of the Earth's crust in the Oaș deep-seated fault area, precipitation parameter variations, water level in the Tysa River in 2019–2020. Research methodology presupposes the use of dynamic characteristics of modern lateral movements of the Earth's crust, spatiotemporal distribution of local earthquakes, observation of precipitation, as well as the comparison of heavy precipitation intervals with periods of seismic intensification. The research uses data obtained in the course of monitoring geophysical observations in the Transcarpathian Inner Trough area, especially at monitoring geophysical stations of the Seismicity Department of the Carpathian region of S.I. Subbotin Institute of Geophysics of the National Academy of Sciences of Ukraine. The data on the movements of the Earth's crust have been obtained at "Korolevo" strainmeter station. The results are significant to study the possible occurrence of local seismicity in the region and to settle the issue of seismically hazardous territories, as well as prediction of seismically hazardous phenomena in the future. The research studies the relation between the dynamic characteristics of modern lateral movements of the Earth's crust in the central part of the Transcarpathian Inner Trough and local seismicity in periods of intensive precipitation. The authors studied the relations between precipitation parameter variations and spatiotemporal distribution of local seismicity in 2019–2020. The analysis of spatiotemporal distribution of local seismicity and precipitation parameter variations in 2020 testifies to a high correlation of geophysical data series: increased amounts of precipitation are accompanied by an increased number of registered local earthquakes in the region; the hydrological aspect of seismotectonic processes in the Transcarpathian Inner Trough has been substantiated. In 2020 rock compression could be observed in the Oaș deep-seated fault area.
Keywords: hydrological state; precipitation; local seismic activity; geodynamic state; earthquakes; modern lateral movements of the Earth's crust